Women and Politics in the Age of the Democratic Revolution - Applewhite, Harriet Branson; Levy, Darline Gay (University of Michigan Press, 1990)
Keywords: 18th century; 18th century; Revolutions; 18th century; Women; Europe; History; Political activity; United States; Women; dept.psc; faculty_collection

Women in Revolutionary Paris, 1789-1795 - Levy, Darline Gay; Applewhite, Harriet Branson; Johnson, Mary Durham (University of Illinois Press, 1979)
"Almost 200 years ago, the women of revolutionary Paris were demanding legal equity in marriage; educational opportunities for girls, including vocational training ; public instruction, licensing, and support for midwives; guarantees for women's rights to employment; and an end to the exclusion of women from certain professions. The editors have uncovered, translated, and annotated sixty documents which shed light on these and other socioeconomic struggles by women and their impact on the French Revolutionary era. This work makes a significant contribution to the growing appreciation of the role of women in history, politics, ideology, and social change."–Back cover.
Keywords: France; History; Paris; Political activity; Revolution; 1789-1799; Sources; Sources; France; Sources; Women; Women's rights; dept.psc; faculty_collection